2015
DOI: 10.1371/journal.pntd.0003795
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Immunotherapy of Secondary Murine Alveolar Echinococcosis Employing Recombinant EmP29 Antigen

Abstract: Alveolar echinococcosis (AE) is caused by infection with the larval stage of the tapeworm Echinococcus multilocularis. An increasing understanding of immunological events that account for the metacestode survival in human and murine AE infection prompted us to undertake explorative experiments tackling the potential of novel preventive and/or immunotherapeutic measures. In this study, the immunoprotective and immunotherapeutic ability of recombinant EmP29 antigen (rEmP29) was assessed in mice that were intrape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 86 publications
2
13
0
Order By: Relevance
“…Such observations are consistent with the effect of TIGIT on the generation of mature immunoregulatory dendritic cells; its role on the inhibition of TNF‐α secretion is also consistent with the dramatic effect of TNF gene deletion shown on E. multilocularis infection susceptibility in mice . Our results are also in line with observations that anti‐PD‐L1 mAb or recombinant EmP29 antigen administration result in a change of Treg and/or T h 2/T h 1 ratio, which may be responsible for partial restriction of metacestode growth . However, in most studies, positive results of immunotherapy were observed when the biotherapeutic agent was administered at time of infection, thus preventing the establishment of the metacestode, which is not applicable to the clinical situation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such observations are consistent with the effect of TIGIT on the generation of mature immunoregulatory dendritic cells; its role on the inhibition of TNF‐α secretion is also consistent with the dramatic effect of TNF gene deletion shown on E. multilocularis infection susceptibility in mice . Our results are also in line with observations that anti‐PD‐L1 mAb or recombinant EmP29 antigen administration result in a change of Treg and/or T h 2/T h 1 ratio, which may be responsible for partial restriction of metacestode growth . However, in most studies, positive results of immunotherapy were observed when the biotherapeutic agent was administered at time of infection, thus preventing the establishment of the metacestode, which is not applicable to the clinical situation.…”
Section: Discussionsupporting
confidence: 91%
“…(40) Our results are also in line with observations that anti-PD-L1 mAb or recombinant EmP29 antigen administration result in a change of Treg and/or T h 2/T h 1 ratio, which may be responsible for partial restriction of metacestode growth. (8,41) However, in most studies, positive results of immunotherapy were observed when the biotherapeutic agent was administered at time of infection, thus preventing the establishment of the metacestode, which is not applicable to the clinical situation. Our results revealed a reduction in the number and size of hepatic infectious lesions with metacestode structures after an anti-TIGIT treatment that was initiated 12 weeks after the beginning of infection, an observation that was rarely reported after chemotherapy or immunotherapy in studies in AE patients and mouse models.…”
Section: Fig 4 In Vitro Tigit Blockade Increases T-cell Response Fomentioning
confidence: 99%
“…Furthermore, EmTIP evoked a strong release of IFN‐γ by CD4 + T cells, hence suggesting that the secretion of this factor as a result of its role in parasite development could ‘secondarily’ induce a potentially protective Th1 response . The most recently identified EmP29 was shown to induce nonspecific in‐vitro T‐lymphocyte proliferation and a lower ratio of Th2/Th1 (IL‐4/IFN‐γ), cytokine mRNA and low mRNA levels of IL‐10 and IL‐2 . Vaccination and active immunotherapy employing rEmP29 antigen had a significant inhibitory effect on the secondary infection with E. multilocularis metacestodes in mice, and yielded thus a reduced parasite infection intensity (load) when compared to mock‐treated control animals .…”
Section: Immunomodulation Triggered By Parasite Components or Metabolmentioning
confidence: 99%
“…The most recently identified EmP29 was shown to induce nonspecific in‐vitro T‐lymphocyte proliferation and a lower ratio of Th2/Th1 (IL‐4/IFN‐γ), cytokine mRNA and low mRNA levels of IL‐10 and IL‐2 . Vaccination and active immunotherapy employing rEmP29 antigen had a significant inhibitory effect on the secondary infection with E. multilocularis metacestodes in mice, and yielded thus a reduced parasite infection intensity (load) when compared to mock‐treated control animals .…”
Section: Immunomodulation Triggered By Parasite Components or Metabolmentioning
confidence: 99%
“…corti endophilin is considerably similar to Echinococcus spp. P29 proteins, which were shown to be highly efficient host protective antigens when used as vaccines [ 51 , 52 ]. A similar role for M .…”
Section: Discussionmentioning
confidence: 99%